2016
DOI: 10.1021/acs.inorgchem.6b00402
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Triggered Cis/Trans Isomerism in Cobalt Dioxolene Chemistry: Distinguishing Effects of Packing on Valence Tautomerism

Abstract: In this article, the synthesis and X-ray crystal structures of two cis/trans isomers of valence tautomeric (VT) cobalt dioxolene compounds are reported. The cis isomer (1) was isolated from the polar protic methanol solvent as a kinetic product, whereas the less polar nonprotic solvent acetone yielded the trans isomer (2). It should be noted that, although some coordination polymers involving cobalt bis(dioxolene) with the cis disposition are known for bridging ancillary ligands, such an arrangement is unprece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 66 publications
4
31
0
Order By: Relevance
“…These studies support the fact that, at higher temperatures, the valence‐tautomeric conversion from manganese(III) tetrabromocatecholate to manganese(II) tetrabromosemiquinonate increases the electrophilic character of the aromatic carbon atom at the para position with respect to the OH group of the semiquinonate ligand and, thereby, favours the aromatic nucleophilic substitution of the Br atom by pyridine. In our recent report, we examined the valence‐tautomeric behaviour of a cobalt(III) tetrabromocatecholate system and found that trans ‐[pyH][Co(Br 4 Cat) 2 (py) 2 ] · 2H 2 O · 2C 3 H 6 O ( A ) is susceptible to a valance‐tautomeric conversion from cobalt(III) tetrabromocatecholate to cobalt(II) tetrabromosemiquinonate at elevated temperatures . Such entropy‐driven valence‐tautomeric conversion is very favourable in the gas or liquid phase.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies support the fact that, at higher temperatures, the valence‐tautomeric conversion from manganese(III) tetrabromocatecholate to manganese(II) tetrabromosemiquinonate increases the electrophilic character of the aromatic carbon atom at the para position with respect to the OH group of the semiquinonate ligand and, thereby, favours the aromatic nucleophilic substitution of the Br atom by pyridine. In our recent report, we examined the valence‐tautomeric behaviour of a cobalt(III) tetrabromocatecholate system and found that trans ‐[pyH][Co(Br 4 Cat) 2 (py) 2 ] · 2H 2 O · 2C 3 H 6 O ( A ) is susceptible to a valance‐tautomeric conversion from cobalt(III) tetrabromocatecholate to cobalt(II) tetrabromosemiquinonate at elevated temperatures . Such entropy‐driven valence‐tautomeric conversion is very favourable in the gas or liquid phase.…”
Section: Resultsmentioning
confidence: 99%
“…The efficient biomimetic catalytic activity of 1 motivated us to examine the catalytic activity of trans ‐[pyH][Co(Br 4 Cat) 2 (py) 2 ] · 2H 2 O · 2C 3 H 6 O ( A ), from which 1 was synthesized, as similar studies with manganese(III) catecholate systems revealed that the positive charge at the ligand backbone significantly enhances the catalytic activity upon pyridyl substitution . However, the time‐dependent spectra for identical reaction condition showed that the biomimetic catalytic activity of A related to the function of phenoxazinone synthase is almost absent (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have explored how the crystal packing governed by different kinds of noncovalent forces affects the valence tautomeric transition in cobalt‐dioxolene systems . Further, the chemistry of manganese complexes with tetrabromocatecholate ligands leads to the formation of robust monoanionic bis(catecholate)‐chelated manganese(III) platforms as major products ,,.…”
Section: Introductionmentioning
confidence: 99%